Recurrent Hydatidiform Moles: A Clinical Challenge-A Case Report and an Update on Management and Therapeutical Strategies - S. Riccio; F. Galanti; M. Scudo; L. Di Troia; M. G. Ferrillo; F. Manzara; P. Ianiri; F. A. Battaglia (Hindawi Limited, 2023)
Hydatidiform mole, complete or partial (CHM/PHM), is the most common type of gestational trophoblastic disease (GTD), which is characterized by excessive trophoblastic proliferation and abnormal embryonic development. Some patients present with sporadic or familiar recurrent hydatidiform moles (RHMs), which are characterized by two or more episodes of the disease. A healthy 36-year-old woman was admitted to the Obstetrics and Gynecology Unit of Santa Maria Goretti Hospital, Latina, because of RHMs at 6 weeks of amenorrhea, with an obstetrical anamnesis of RHMs. We performed uterine dilatation and curettage with suction evacuation. The histological examination confirmed the diagnosis of PHM. The clinical follow-up was conducted according to recent guidelines on the diagnosis and management of GTD. After the return to the baseline values of the beta-human chorionic gonadotropin hormone, a combined oral contraceptive therapy was proposed, and the patient was invited to undergo in vitro fertilization (IVF) techniques, specifically oocyte donation, to reduce the possibility of similar future cases of RHMs. Although some etiopathogenetic mechanisms involved in RHMs are still unknown, all patients of childbearing age who are affected by this syndrome should be properly treated and directed towards a correct clinical path as IVF, to have a successful and safe pregnancy.